Muslim funeral rights in The West - Hussain, Nouman (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2024)
This paper examines the rights of the deceased from a Sunni jurisprudential perspective and its application in selected Western nations. Despite the growing Muslim population in the West since World War II, scholarly attention has predominantly focused on topics such as extremism, Islamophobia, and minority jurisprudence, with minimal exploration of death-related matters. This paper addresses this gap by delving into the Islamic rulings concerning death and dying and their implications for Muslims living in Western societies. By examining issues such as burial rights, this research aims to provide valuable insights into how Muslims can navigate the complexities of death within Western legal and cultural frameworks. Through a comprehensive analysis of Sunni jurisprudence, this study seeks to offer practical guidance for Muslims facing end-of-life situations in non-Muslim majority environments.